Desert roses: cultivating to empower - Yamaguchi, Hudinilson Kendy de Lima (2024)
Women's empowerment actions go beyond physical aspects and encompass issues of financial independence and emotional autonomy. This project aimed to empower and motivate socially vulnerable women towards entrepreneurship through outreach actions, with a view to training and technical and professional capacity building on the production, cultivation, and commercialization of Desert Roses (Adenium obesum) and their various by-products and inputs. The project was developed between November 8 and 26, 2021,  through educational practices in the form of an Initial and Continued Training (FIC) course, using a theoretical-practical teaching methodology, in addition to the Prior Learning Assessment and Recognition System (ARAP). The activity targeted 25 women from the municipality of Coari-Amazonas and included theoretical courses, workshops, and evaluative activities. As a result, there was stimulation of women’s educational, productive, and social inclusion, qualifying them for the managing and cultivating of Desert Roses and the various by-products of their production chain.  This encouraged entrepreneurship and women's empowerment.